Habitat selection and spatiotemporal interactions of a reintroduced mesocarnivore. Issue 5 (13th May 2019) - Parsons, Mitchell A.; Lewis, Jeffrey C.; Gardner, Beth; Chestnut, Tara; Ransom, Jason I.; Werntz, David O.; Prugh, Laura R.
ABSTRACT: Habitat quality and quantity are key factors in evaluating the potential for success of a wildlife translocation. However, because of the difficulty or cost of evaluating these factors, habitat assessments may not include valuable information on important habitat attributes including the abundance and distribution of prey, predators, and competitors. Fishers ( Pekania pennanti ) are one of the most commonly reintroduced carnivores in North America, and they are a species of conservation concern in their western range. We examined the relative importance of landscape features and species interactions in determining habitat use of a reintroduced population of fishers in the southern Cascade Mountains, Washington, USA. We used detections of prey and predators at 134 remote camera stations, remotely sensed forest structure data, and telemetry locations of fishers in a resource selection function to assess the relative importance of prey, predators, and forest structure in fisher habitat selection. Fishers selected habitats based on forest conditions and activity levels of snowshoe hares ( Lepus americanus ), whereas bobcat ( Lynx rufus ) and coyote ( Canis latrans ) activity levels did not directly affect habitat selection. The probability of fisher use increased in older stands, close to recently disturbed stands, and in areas with intermediate levels of hare activity. Bobcat and hare activity levels were positively correlated, and fishers avoided areas with the greatest hare activity, suggesting that fishers may experience a food‐safety tradeoff in the study area. Temporal activity patterns in photo detections indicate that fishers may mediate this danger by avoiding bobcats temporally. Our findings suggest that fishers in Washington prefer habitat mosaics of old and recently disturbed stands where they have greater access to resting structures and hares. Management that maintains mosaics of young and old forest across large landscapes is likely to support fisher recovery. Future reintroduction efforts would benefit from an assessment of prey and predator abundance in proposed reintroduction areas before project initiation. © 2019 The Wildlife Society. Abstract : We assessed habitat selection of reintroduced fishers in Washington, USA, and documented selection for mature forests that were near young stands and moderate abundance of a major prey item. Our results also indicate a potential food‐safety tradeoff for fishers, which they may mediate through temporal segregation from bobcats.